Profile of Prospective Biology Teacher's Critical Thinking Skills as an Effort to Prepare 21st Century Generations - Hidayat, Syibli; Umam, Muhammad Masholihul; Fitriati, Ananda Putri; Sa'idah, Alifatus; Mirafsur, Vivi Amelia (Aspirasi Masyarakat Intelektual Islam Nusantara, 2023)
The purpose of this study was to assess the degree of critical thinking skills for prospective biology instructors in the Plant Biosystematics course as starting knowledge in order to better educate the twenty-first century generation. This study was carried out as part of the Plant Biosystematics course at UIN KHAS Jember. The descriptive research method with a quantitative approach was adopted. Random sampling was utilized as the sample strategy. A multiple-choice test is used to acquire the critical thinking assessment instrument, which relates to six critical thinking skills. The results revealed that the critical thinking abilities of biology teacher candidates recorded 54 and 68.1 on the Good scales, but needed to be developed further. Whereas the skills to analyze and explain have a score of 63 and 40.9 with sufficient criteria, respectively, they still require a lot of improvement in order for the criteria to become higher, while self-regulation skills have a score of 63 with very sufficient criteria, but these self-regulation skills should be more than enough because self-regulation is very important for individuals. This demonstrates that Biology students at UIN KHAS Jember must develop their critical thinking abilities, which will be required in the twenty-first century.